Secessionist Entities and International Law : The South Caucasus Disputes between Self-Determination, Territorial Integrity, and the Quest for a European Engagement Policy - C. Harzl, Benedikt (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
This book examines secessionist entities that arose during and after the dissolution process of the USSR and considers them as legal subjects in their own right. By employing a novel and more innovative approach, the agency of these subjects, otherwise often ignored or disregarded, is taken into account. Drawing on the cases of the South Caucasus, the author suggests going beyond the binary concept of statehood and traditional notions of sovereignty. He advocates embracing an inclusive reading of international law, which enables to foster creative ambiguity vis-à-vis these entities as means of conflict transformation.